Recommendations included in the Decisions on the need for special education of pupils with visual impairment and their implementation by the school - Kokot-Rybińska, Magdalena (Disability and education, 2023)
Decisions on the Need for Special Education have been functioning in Poland for over 30 years, and in an almost unchanged form (Journal of Laws No. 95, item 425 of September 7, 1991, Law on the Education System). It would seem, then, that the education system had enough time to adapt to this form of providing support to pupils of mainstream education. Unfortunately, despite numerous reforms, programs and directions for the development of the system of equalizing educational opportunities, a student with special educational needs still has to deal with numerous shortcomings or even omissions on the part of the teaching staff and the management of the school. The aim of this study is to present the difficulties faced by pupils with visual impairments in the implementation of the recommendations of the Decisions on the Need for Special Education in mainstream schools. This article was created based on the analysis of data collected through the proprietary questionnaire on the assessment of the implementation of recommendations on the need for special education by schools. The content of the recommendations contained in the decisions issued by the state Psychological and Pedagogical Counseling Centers, which were made available by the respondents, was also analyzed.